Implementasi Sistem Pengendali Jari Tangan Robot Dengan Sensor Flex Menggunakan Metode Map - Galang Eiga Prambudi; Rizal Maulana; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This study aims to assist human work in conducting activities that are dangerous to touch human hands such as taming the bombs, removing dangerous objects such as test tubes that contain harmful chemical active substances that can endanger human harmony. At the input value the developer uses a flex sensor. Flex sensor is a sensor that has a function in detecting a principle curvature. Developers choose the flex sensor due to a need to get motion values ​​on the finger arch. In making it easier to find the full picture of the idea and ideas, added a method in the design system, the method used is the map method. The map method is a concept map that is responsible for collecting all the important data on the program concept which is then collected in one data. The map method is used because it has a simple concept and is not complicated enough than other methods. In designing the system created then obtained the conclusions to read the value of the movement on the flex sensor for movement to get the average value of 213.4. In a hand-held test for a sponge object requiring values ​​of 163 to 196, a bottle object of 150 to 162 and to a rock object requires a value of 124 to 137. In a handheld robber test the results of the presentation of the system are able to obtain 100% valid results. In the handheld bottle power object get 100% valid result. While on the stone object get percentage of handheld power by 60%.